PROBLEMATIKA PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 TK X DI SURABAYA - Jeane Eirene (MOTORIC, 2023)
The right learning system is one of the successes in learning objectives, but during theCOVID-19-19 pandemic, it creates problems between teachers and parents. This studyaims to find out the problems of online learning in Tk X Surabaya, Using qualitativeresearch types with a descriptive approach, data collection techniques using observation,interviews, documentation. The result of this study is that there are learning problems inparents and teachers during online learning.Keywords: problems of online learning; Preschool ; COVID-19-